PENERAPAN MODEL PEMBELAJARAN TIPE BERTUKAR PASANGAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 10 PEKANBARU - Wahyuni, Gusti; Azmi, Jonni; Rery, R Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to increase student learning achievement on the topic of hidrocarbon in class X Senior High School Negeri (SMAN) 10 Pekanbaru. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class X 5 as the experimental class and students of class X 8 as the control class. Experimental class is a class that is applied to learning model cooperative exchanged couples type while the control class was not. Data analysis technique used is the t-test and Kp test. Based on data analysis of data obtained tcount > ttable is 1,70>1.66, means that model cooperative echanged couples type can improve student learning achievement on the topic of hidrocarbon in class X Senior High School Negeri (SMAN) 10 Pekanbaru. The results showed that the implementation of learning model cooperative exchanged couples type can improve student achievement with an increase of 1,22%.Key Words : Learning Achievement, Learning model cooperative exchanged couples type, Hidrocarbon